Holocaust poetry : awkward poetics in the work of Sylvia Plath, Geoffrey Hill, Tony Harrison and Ted Hughes /: awkward poetics in the work of Sylvia Plath, Geoffrey Hill, Tony Harrison and Ted Hughes. ([2019?]) - Rowland, Antony
No abstract available